2022
DOI: 10.3390/ijms232012066
|View full text |Cite
|
Sign up to set email alerts
|

Diclofenac Sensitizes Signet Ring Cell Gastric Carcinoma Cells to Cisplatin by Activating Autophagy and Inhibition of Survival Signal Pathways

Abstract: Gastric cancer has one of the highest incidence rates of cancer worldwide while also contributing to increased drug resistance among patients in clinical practice. Herein, we have investigated the role of diclofenac (DCF) on sensitizing cisplatin resistance in signet ring cell gastric carcinoma cells (SRCGC). Non-toxic concentrations of DCF significantly augmented cisplatin-induced cell death in cisplatin-resistant SRCGC cells (KATO/DDP) but not in cisplatin-sensitive SRCGC cells (KATOIII). Consistently, conco… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 46 publications
0
3
0
Order By: Relevance
“…Some well-known NSAIDs are already being repurposed: they can be used not only in the treatment of cancer-related pain but also as anticancer drugs and chemosensitizing drugs [ 24 , 41 , 51 ]. The cytotoxic action of NSAIDs is realized via different mechanisms: a decrease in the expression of MYC (a family of regulator genes and protooncogenes that code for transcription factors), the regeneration of intracellular ROS and induction of apoptotic death, cell cycle arrest at different checkpoints, the inhibition of cell proliferation and migration, activating autophagy, and microtubule destabilization [ 29 , 52 ]. DCF also sensitizes cancerous cells to cisplatin and 5-fluorouracil [ 41 , 52 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Some well-known NSAIDs are already being repurposed: they can be used not only in the treatment of cancer-related pain but also as anticancer drugs and chemosensitizing drugs [ 24 , 41 , 51 ]. The cytotoxic action of NSAIDs is realized via different mechanisms: a decrease in the expression of MYC (a family of regulator genes and protooncogenes that code for transcription factors), the regeneration of intracellular ROS and induction of apoptotic death, cell cycle arrest at different checkpoints, the inhibition of cell proliferation and migration, activating autophagy, and microtubule destabilization [ 29 , 52 ]. DCF also sensitizes cancerous cells to cisplatin and 5-fluorouracil [ 41 , 52 ].…”
Section: Discussionmentioning
confidence: 99%
“…The cytotoxic action of NSAIDs is realized via different mechanisms: a decrease in the expression of MYC (a family of regulator genes and protooncogenes that code for transcription factors), the regeneration of intracellular ROS and induction of apoptotic death, cell cycle arrest at different checkpoints, the inhibition of cell proliferation and migration, activating autophagy, and microtubule destabilization [ 29 , 52 ]. DCF also sensitizes cancerous cells to cisplatin and 5-fluorouracil [ 41 , 52 ]. The chemosensitizing activity of NSAIDs is due to the inhibition of both the expression and enzyme activity of SOD2 and COX-2.…”
Section: Discussionmentioning
confidence: 99%
“…It has been shown that diclofenac, a nonsteroidal anti-inflammatory drug, enhances cisplatin cytotoxicity in signet ring cell gastric carcinoma cells. The use of diclofenac in combination therapy with cisplatin significantly increases ROS-induced macroautophagy [ 10 ]. Aiming to improve the cancer pharmacological approach, a pilot study demonstrated, in a neuroblastoma xenograft model, the strengthening of cisplatin effects when administered as cocktail therapy with acetazolamide, a carbonic anhydrase isoform IX inhibitor, and fendiline hydrochloride, an inhibitor of several transporters involved in multidrug resistance of cancer cells [ 11 ].…”
mentioning
confidence: 99%